THE CHANGING LANDSCAPE OF CHROMOSOME MARKERS. (February 2015) - Azmanov, Dimitar N.; Ngo, Con; Sivamoorty, Soruba; Britton, Vikki; Peverall, Joanne; Woodward, Karen; Murch, Ashleigh; Ravine, David; Mina, Kym
Abstract : The phenomenon of multiple supernumerary marker chromosomes (SMCs) is a rare event (http://ssmc-tl.com/sSMC.html). It is typically accompanied by somatic mosaic variation in the number of intracellular marker chromosomes and their morphology. This dynamic variation is associated with mitosis and complicates diagnosis, as well as predictions of the clinical severity. Until now, the mechanism of SMC formation remains poorly understood, with associated uncertainties about the familial recurrence risk. We describe a paediatric patient with multiple congenital abnormalities and developmental delay associated with dynamic mosaicism for up to three SMCs. Using a combination of conventional and molecular cytogenetic techniques, we clarified the origins of SMCs from five different genomic locations (1q21.1q21.3, 1q21.3q22, 8q11.1q11.23, 9p13.1p12 and 14q11.2). SNP microarray data and family-trio analysis excluded the possibility of secondary uniparental disomy, which may sometimes occur as a result of an accompanying chromosomal rescue event. It also demonstrated that the markers were of maternal origin and consistent with a meiosis II error. Our observations, in concert with published findings from in vitro fertilisation experiments, allow us to propose a novel mechanism to explain the origin of multiple SMCs.